The Implementation Of The Word-For-Word Translation Method To Enrich Students’ Vocabulary Mastery - umar, umar; Desianti Ma’tan (Cita konsultindo, 2022)
This study aimed to determine the enrichment in students' vocabulary after the implementation of the word-for-word translation method and to determine the student's response to the implementation of the word-for-word translation method. The location of this research was in SMP Negeri 1 Pana. The approach used in this research was quantitative with a quasi-experimental and survey methodology. Sampling used simple random sampling and the sample was the entire class VIII which collected 46 people. Class VIII A was the experimental class consisting of 23 people and class VIII B was the control class consisting of 23 people. The experimental class applied the word-for-word translation method while the control class used the free translation method. This study used instrument tests and questionnaires. The mean score of the pre-test students was (25,13) and the mean score of the post-test was (42,52), while the results of the Independent T-Test showed that Sig. (2-tailed) < 0.05 or (0.00 < 0.05) so it can be concluded that the implementation of the word-for-word translation method can enrich students' vocabulary. For the analysis of the questionnaire, the student's responses were in the Good category where the average value was 75,0. This means that students are interested and have a positive perception of using the word-for-word translation method to enrich students' vocabulary